Do alternative work arrangements substitute standard employment? Evidence from worker-level data - Bernardo Fanfani; Filippo Passerini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2024)
This study analyses the impact of an Alternative Work Arrangement (AWA) called "voucher" on earnings of atypical workers and on their alternative income sources using Italian administrative data. Specifically, we investigate whether this form of very flexible work substitutes income from more standard labor contracts and welfare transfers related to employment insurance (sick and parental leave and unemployment benefits). We estimate cross-income elasticities using fixed effects and diff-in-diff specifications that correct for sample selection of individuals in the labor market. Results show that vouchers increase overall labor income, but they also substitute earnings derived from other labor contracts. We do not find relevant associations between vouchers and welfare transfers. The positive effect of vouchers on total income is smaller in specifications that correct for sample selection bias, and the substitution effect with other labor income sources is substantially larger. Overall, our findings show that AWAs tend to substitute standard employment, with small positive net effects on earnings, which are larger for intensive users of vouchers, and in geographic regions with a more sizable informal sector.
Keywords: J24; J22; D12; C13; C21; 330; Alternative work arrangements; labor supply; cross-income elasticity; sample selection; difference-in-differences; event-study